Etika dalam Penelitian Pedidikan - Nur Hafiza Sibarani; Meyniar Albina (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study discusses the importance of ethics in educational research, which serves as the fundamental basis for maintaining scientific integrity and protecting the rights of research subjects. The study aims to examine the principles of research ethics in education, the challenges faced in its implementation, and solutions to ensure compliance with ethical standards. This research employs a literature review method by analyzing various relevant sources. The findings indicate that the key principles of research ethics in education include respect for research subjects, maintaining privacy and data confidentiality, upholding objectivity, and ensuring transparency in reporting results. Common challenges encountered include protecting participants' rights, avoiding bias, and managing conflicts of interest that may affect research validity. Therefore, researchers must possess a high level of awareness and responsibility to ensure that their research provides positive benefits for academia and society at large